PRAKTIK TRADISI MA’TINGGORO TEDONG DI TANA TORAJA PERSPEKTIF FIKIH PENYEMBELIHAN DALAM ISLAM - Azwan; Nurinayah (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2024)
Ma'tinggoro is a tradition of slaughtering or slaughtering animals, especially buffalo, the ma'tinggoro tradition can be found in the Tana Toraja area which has the ma'tinggoro process in traditional ceremonies, namely the solo sign. The research method used in this study uses descriptive qualitative research. The data source in this study used data from interviews, observations, documentation and literature reviews. In the interview activity involving the secretary of the MUI Tana Toraja who was the main informant in this study, the results of the research described that the practice of the ma'tinggoro tradition is a tradition carried out in the slaughter of animals, especially buffalo and is usually found during the Wednesday Solo traditional ceremony.